SUPPORTIVE GROUP THERAPY TO REDUCE PUBLIC SPEAKING ANXIETY IN ADOLESCENTS - Ika Annisa Elvira; Elli Nur Hayati (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
This study aimed to discover the effect of supportive group therapy to reduce public speaking anxiety on adolescents. The subjects in this study were five female adolescents of 17- to 19-year-olds. The study method used was an experimental study with the one-group pretest-posttest design using the purposive sampling technique. The study instrument used was the scale produced by Israwanda [9] based on Rogers’ [13] theory with public speaking anxiety aspects, i.e., physical responses, emotions, and mental processes. The non-parametric analysis test was using the Wilcoxon analysis technique to discover the differences between the pretest-posttest. The analysis result obtained was 0.043, which is <0.05. It shows a reduction of public speaking anxiety in adolescents. It is concluded that supportive group therapy implementation can reduce public speaking anxiety in adolescents